2011
DOI: 10.1093/humrep/der096
|View full text |Cite
|
Sign up to set email alerts
|

No difference in markers of adipose tissue inflammation between overweight women with polycystic ovary syndrome and weight-matched controls

Abstract: BACKGROUNDPrevious studies have indicated that peripheral circulating markers of inflammation are elevated in women with polycystic ovary syndrome (PCOS), but thus far no studies concerning markers of inflammation in adipose tissue have been published. The aim of the study was to investigate whether patients with PCOS display increased expression of inflammatory markers in adipose tissue.METHODSTwenty overweight patients with PCOS, 10 lean patients with PCOS and 20 overweight controls had subcutaneous fat biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
34
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 57 publications
5
34
2
Order By: Relevance
“…In a recent study, Lindholm et al (38) found no difference in markers of inflammation in adipose tissue between obese women with and without PCOS, which corresponds to our findings. In contrast, Carmina et al (39) described reduced expression of both adiponectin and leptin in subcutaneous adipose tissue in women with PCOS compared with control women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In a recent study, Lindholm et al (38) found no difference in markers of inflammation in adipose tissue between obese women with and without PCOS, which corresponds to our findings. In contrast, Carmina et al (39) described reduced expression of both adiponectin and leptin in subcutaneous adipose tissue in women with PCOS compared with control women.…”
Section: Discussionsupporting
confidence: 92%
“…Because subclinical inflammation is regarded as a cardiovascular risk factor, interest has focused on the role the two inflammatory mediators IL-6 and TNF-a in the development of cardiovascular disease. The data on IL-6 and TNF-a in PCOS have been conflicting (38,(52)(53)(54), and we found no effect of PCOS on either TNF-a or IL-6.…”
Section: Discussioncontrasting
confidence: 72%
“…However, we do not find that the expression levels of IL6 mRNA were significantly different between women with PCOS and normal control women. Findings from this study seem to contrast with the reports from the laboratories of Lindholm et al (30). They showed that overweight rather than the PCOS diagnosis per se appears to be the main explanatory variable for elevated adipose tissue inflammation in patients with PCOS.…”
Section: Discussioncontrasting
confidence: 99%
“…According to some research, overweight, rather than the PCOS diagnosis per se, appears to be the main explanatory variable for elevated adipose tissue inflammation in patients with PCOS [32]. On the other hand PCOS obese and non-obese patients show higher serum MCP-1 levels than controls [15].…”
Section: Discussionmentioning
confidence: 99%